An improved droop control with network adaptive ability in islanded mode of microgrid. Issue 1 (December 2020) - Li, Shengwen; Wang, Jinhao; Wang, Hao; Zhang, Ying; Lei, Da; Wang, Tan; Gao, Le
Abstract: When the microgrid operates in island mode, the droop control can be adopted to realize effective power distribution among distributed generations (DGs). Due to the different line impedancesof the various DGs, disproportional power distribution and circulating currents occur in conventional droop control, which make it difficult to maximize the efficiency of DGs and even may cause some DGs overloads. Therefore, an improved droop control strategy with an adjustable droop coefficient is proposed. The relationship between line impedance and reactive power is obtained by analysing conventional droop control. Then a new droop control algorithm is proposed. By introducing the output reactive power information of other DGs into the integral feedback link, the droop coefficient is modified to realize the accurate distribution of reactive power. The model is built on the Matlab/Simulink platform, and the effectiveness of the proposed control strategy is verified by comparing its reactive power distribution resultwith that of the conventional droop control.